Selection of ornamental glandularia hybrids potentially used as pot or bedding plants - Imhof, Lelia (2018)
As part of the breeding program of Glandularia (Verbenaceae), here we performed interspecific crosses to select the most outstanding materials and define trait associations for descriptors related to ornamental performance. The experimental material consisted of populations of three species of Glandularia and their offspring. Crosses were obtained by artificial hybridization using the diallel method. Reproductive efficiency values ranged from 10.4% to 60.7%. Ornamental characterization on pot and bedding plants were obtained from hybrids and their parents, after analysation through a principal components analysis. The pot plant fitness index values for parents and offspring ranged between 0.56–0.76 and 0.56–0.78, respectively; the bedding index values for parents and offspring ranged between 0.17–0.99 and 0.15–0.99, respectively. The features selected for the construction of the indices were effective for discriminating the ornamental aptitude of the different plant materials. Glandularia hybrids showed a remarkable ornamental performance for different purposes, some hybrids performing better as pot plants, others for bedding plants, and some for both.